Antibiotic Resistance in Acetic Acid Bacteria Originating from Vinegar - Sun-Hee Kim; Hyun-Wook Jang; Jin-Ju Park; Dong-Geon Nam; Su-Jeong Lee; Soo-Hwan Yeo; So-Young Kim (MDPI AG, 2024)
Acetic acid bacteria (AAB) are major contributors to the production of fermented vinegar, offering various cultural, culinary, and health benefits. Although the residual unpasteurized AAB after vinegar production are not pathogens, these are necessary and require safety evaluations, including antibiotic resistance, before use as a starter. In this research, we investigated the antibiotic resistance profiles of 26 AAB strains, including various species of Komagataeibacter and Acetobacter, against 10 different antibiotics using the E-test method. All strains exhibited resistance to aztreonam and clindamycin. Komagataeibacter species demonstrated a 50% resistance rate to ciprofloxacin, analogous to Acetobacter species, but showed twice the resistance rates to chloramphenicol and erythromycin. Genomic analysis of K. saccharivorans CV1 identified intrinsic resistance mechanisms, such as multidrug efflux pumps, thereby enhancing our understanding of antibiotic resistance in acetic acid-producing bacteria. These findings enhance understanding of antibiotic resistance in AAB for food safety and new antimicrobial strategies, suggesting the need for standardized testing methods and molecular genetic study.